2019
DOI: 10.1016/j.neuroimage.2019.03.070
|View full text |Cite
|
Sign up to set email alerts
|

False-positive neuroimaging: Undisclosed flexibility in testing spatial hypotheses allows presenting anything as a replicated finding

Abstract: Hypothesis testing in neuroimaging studies relies heavily on treating named anatomical regions (e.g., "the amygdala") as unitary entities. Though data collection and analyses are conducted at the voxel level, inferences are often based on anatomical regions. The discrepancy between the unit of analysis and the unit of inference leads to ambiguity and flexibility in analyses that can create a false sense of reproducibility. For example, hypothesizing effects on "amygdala activity" does not provide a falsifiable… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…One approach may be to use parametric modulators, which has been used in prior analyses, but is largely underutilized (Aloi et al, 2019;Joseph et al, 2016). In addition to improving estimates of functional parcels (Nikolaidis et al, 2020), multivariate pattern analyses may help with the reproducibility of theorized cognitive processes (Hong et al, 2019). Multivariate, cross-validated, pattern analyses can provide a priori activation patterns and locations that can be confirmed out of sample, reducing the possibility of exploring multiple hypotheses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One approach may be to use parametric modulators, which has been used in prior analyses, but is largely underutilized (Aloi et al, 2019;Joseph et al, 2016). In addition to improving estimates of functional parcels (Nikolaidis et al, 2020), multivariate pattern analyses may help with the reproducibility of theorized cognitive processes (Hong et al, 2019). Multivariate, cross-validated, pattern analyses can provide a priori activation patterns and locations that can be confirmed out of sample, reducing the possibility of exploring multiple hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has suggested that analytic methods and decisions may not only alter outcomes, but also result in different interpretations of fMRI analyses. For instance, Hong et al (2019) found that peak level coordinates from various studies have a high degree of variability, that may often lead to inaccurate conclusions about replication. Although activations may be close in distance between two groups (or studies), such that they appear to be in similar brain regions, these may not be related to a 'replication' of a neural process that is hypothesized, due to a lack of neural specificity.…”
Section: Differential Use and Research Degrees Of Freedom In Mid Taskmentioning
confidence: 99%
“…Further, the significant replication of results, despite the age mismatch between the Discovery and Replication cohorts, may suggest that the observed effects are robust to differences in age. Our approach using a specific, pre‐defined composite cluster was not subject to the “model degrees of freedom” which purportedly have driven false‐positive replications in neuroimaging (Hong, Yoo, Han, Wager, & Woo, ). Last, our study did not make use of multivariate data mining or machine learning approaches which are gaining popularity with application in prediction studies, and show high levels of accuracy (Benedict et al, ; Dyrba et al, ; Moradi, Pepe, Gaser, Huttunen, & Tohka, ).…”
Section: Discussionmentioning
confidence: 99%
“…Frequently, the rationale supporting ROI selection is based on vague statements or on citing previous findings without motivating how these suggest an association between a well-defined brain area and a specific mental process. Across the neuroimaging literature, it is unclear how many published papers rely on an adequate definition of ROIs (Hong, Yoo, Han, Wager, & Woo, 2019). Hypothetically, the choice of any ROI may be justified based on the existing literature, leading to a "garden of forking paths" of potential data-dependent analyses (Gelman & Loken, 2014).…”
mentioning
confidence: 99%
“…Useful tools in this regard are represented by GingerALE (Müller et al, 2018) and Seed-based d Mapping (SDM; Albajes-Eizagirre, Solanes, Vieta, & Radua, 2019), which quantitatively aggregate neuroimaging findings, as well as by Neurosynth (Yarkoni, Poldrack, Nichols, Van Essen, & Wager, 2011) and NeuroQuery (Dockès et al, 2020), which estimate the association between voxels and terms semantically related to the study hypothesis or to functional areas of interest (e.g., fusiform face area). The definition of ROIs could also be based on inherently vague anatomical terms (e.g., medial prefrontal cortex) or it may refer to a large patch of the cortex (e.g., precise location within the Superior Frontal Gyrus; Hong et al, 2019). Interestingly, Neurosynth and Neuroquery can be used to precisely define anatomical ROIs, which have no clear boundaries or are typically not included in anatomical atlases, as the temporo-parietal junction (Lettieri et al, 2019).…”
mentioning
confidence: 99%